A pilot study of the use of human amniotic membrane as subcutaneous implants in a mouse model: a potential for temporary substitutes in two-stage breast reconstructions - Sadaf Alipour; Ramesh Omranipour; Bita Eslami; Solmaz Khalighfard; Azin Saberi; Azar Shabestari; Ali Mohammad Alizadeh (BMC, 2023)
Abstract Introduction Breast reconstruction by prosthesis is frequently performed in breast cancer treatments, and a temporary substitute is used in the first step of two-stage operations. Aim Due to the advantageous biological features of the human amniotic membrane, we aimed to evaluate its use for temporary implants. Method We prepared small spherical implants from human amniotic membranes and inserted them into BALB/c mice's subcutaneous flanks. Then, we compared the bulging they produced, the durability, and the host reaction with implants made from the chorionic membrane, folded membrane patches, and sterile plastic beads. Results All amionitic cases were healthy throughout the study and only mild inflammation occurred in them. Furthermore, the bulging of the implants was acceptable and faded gradually. However, moderate inflammation was observed in chorionic implant mice, and the bulging disappeared very soon. Finally, the control group had severe inflammation and the beads implant was rejected. Conclusion Our study showed that the human amniotic membrane could represent a safe and valid tool for breast reconstruction, however, further studies on larger animals and more implants are suggested.